Groupthink or deadlock : when do leaders learn from their advisors? - Kowert, Paul, 1964- (SUNY series in the presidency., 2002)
"The danger of groupthink is now standard fare in leadership training programs and a widely accepted explanation, among political scientists, for policy-making fiascoes. Efforts to avoid groupthink, however, can lead to an even more serious problem - deadlock. Groupthink or Deadlock explores these dual problems in the Eisenhower and Reagan administrations and demonstrates how both presidents were capable of learning and consequently changing their policies, sometimes dramatically, but at the same time doing so in characteristically different ways. Kowert points to the need for leaders to organize their staff in a way that fits their learning and leadership style and allows them to negotiate a path between groupthink and deadlock."--Jacket